Apocrine secretion: New insights into an old phenomenon - Farkas, Róbert (Biochimica et biophysica acta, 2015)
While apocrine secretion was among the earliest secretory mechanisms to be identified, its underlying basis remains poorly understood. This review reappraises our understanding of apocrine secretion using insights about apocrine secretion from the salivary glands of Drosophila, in which molecular genetic analyses have provided a glimmer of hope for elucidating the mechanistic aspects of this fundamental process. In contrast to the well-defined process of exocytosis, apocrine secretion is non-vesicular transport and secretory pathway that entails the loss of part of the cytoplasm. It often involves apical protrusions and generates cytoplasmic fragments inside a secretory lumen. In its most intense phase this process is accompanied by the release of large fragments of cellular structures and entire organelles that include mitochondria, Golgi, and portions of the endoplasmic reticulum, among others. Proteomic analyses revealed that the secretion is composed of hundreds to thousands of membranous, cytoskeletal, microsomal, mitochondrial, ribosomal, and even nuclear as well as nucleolar proteins. Strikingly, although many nuclear proteins are released, the nuclear deoxyribonucleic acid itself remains intact. In spite of this complexity, it appears that several protein components of apocrine secretion are identical, regardless of the location of the apocrine gland. This type of secretion appears to be common to many, if not all, barrier epithelial tissues including skin derivatives and the epididymis, and is implicated also in lung/bronchi and intestinal epithelium. Apocrine secretion is a mechanism that provides the en masse delivery of a very complex proteinaceous mixture from polarized epithelial tissues to allow for communication at exterior interfaces. [Display omitted] •Apocrine secretion is nonvesicular transport and secretory mechanism.•Apocrine secretion takes place by discharging a portion of the cell contents.•Secretory material is a highly complex protein mixture from all cellular compartments.•It is observed in polarized epithelial tissues of metazoans, not in individual cells.•These secretory products serve at interface barrier to communicate with the exterior.